IMPLEMENTASI KEBIJAKAN TENTANG PENGELOLAAN SAMPAH - Zulfa, Agra Alfin; Rahmawati, Rita; Purnamasari, Irma; Hernawan, Denny; Wahyudin, Cecep; Apriliani, Afmi; Ramdani, Faisal Tri; Syahrudin, Dede; Saepudin (Jurnal Governansi, 2025)
Waste management in urban buffer areas such as Ciawi District, Bogor Regency, has become a critical issue due to increasing population growth and the intensification of community activities. To address this challenge, the Bogor Regency Government enacted Regional Regulation Number 2 of 2014 on Waste Management. However, the implementation of this regulation has not been optimal, facing various structural and operational obstacles on the ground. This study evaluates the effectiveness of the policy implementation using George C. Edward III’s policy implementation theory, which includes four key dimensions: communication, resources, disposition, and bureaucratic structure. A quantitative survey method was employed, utilizing the Weighted Mean Score (WMS) analysis on 16 employees of the Waste Management Technical Implementation Unit (UPT) Region III and 100 residents of Ciawi District. The results show a significant disparity in assessments between implementers and the community. While officials rated disposition and bureaucratic structure very positively, residents perceived disposition as merely good and rated communication and resources relatively low. These findings indicate weaknesses in information dissemination and a lack of adequate facilities and workforce support. Therefore, improving the effectiveness of waste management policy requires enhanced participatory communication, sufficient resource provision, and stronger institutional synergy to achieve efficient and sustainable waste management in the region.